A pilot study of MBA programmes in South Africa. (1st November 2019) - Muposhi, Asphat; Dhurup, Manilall; Martin, Robert; Bhadury, Joyendu
In recent years, Master of Business Administration (MBA) programmes and their curricula have been subjected to substantial scrutiny. However, the majority of studies have been confined to business schools in Western countries. By comparison, much less research is available on MBA programmes in developing countries, particularly those in Africa. In an effort to address this gap, this article examines MBA programmes in South Africa by first situating them within the global MBA curriculum debate. It then notes the need to move away from a generalist MBA programme to a specialized MBA in line with emerging global trends. Finally, it suggests a multidisciplinary approach to the redesign of the MBA curriculum.